Identification of Stomata Structures in Leaves of The Tradescantia Genus in The Meurandeh Langsa Region - M. Ali Akbar; Khairunnisa; Enca Pepayosa; Amanda Lestari; Sahna Maulana Sitakar; Viska Annisa Sabrini; Rauzatul Jannah Mz; Siti Zubaida; Siska Rita Mahyuny (Jurnal Biologi Tropis, 2023)
Langsa City is a city located in the province of Nangroe Aceh Darussalam with an area of 262.41 km2 with a population of 165,890 people. Meurandeh Village is one of the villages located in Langsa city, precisely in Langsa Lama. Meurandeh is one of the places that produces plants from the Tradescantia genus. This research aims to identify and differentiate the stomata of three types of plants from the Tradescantia genus. The method used in this research is a qualitative method with observational data collection techniques. The results of this research show that the three types of plants from the Tradescantia genus have three neighboring cells and a tetracytic type of stomata. Of these three types of plants, there are differences in the shape and structure of the stomata.